Childhood body size and pubertal timing in relation to adult mammographic density phenotype. Issue 1 (December 2017) - Schoemaker, Minouk; Jones, Michael; Allen, Steven; Hoare, Jean; Ashworth, Alan; Dowsett, Mitch; Swerdlow, Anthony
Abstract Background An earlier age at onset of breast development and longer time between pubertal stages has been implicated in breast cancer risk. It is not clear whether associations of breast cancer risk with puberty or predictors of onset of puberty, such as weight and height, are mediated via mammographic density, an important risk factor for breast cancer. Methods We investigated whether childhood body size and pubertal timing and tempo, collected by questionnaire, are associated with percentage and absolute area mammographic density at ages 47–73 years in 1105 women recruited to a prospective study. Results After controlling for adult adiposity, weight at ages 7 and 11 years was strongly significantly inversely associated with percentage and absolute dense area (p trend <0.001), and positively associated with absolute non-dense area. Greater height at age 7, but not age 11, was associated with lower percentage density (p trend = 0.016). Later age at menarche and age at when regular periods were established was associated with increased density, but additional adjustment for childhood weight attenuated the association. A longer interval between thelarche and menarche, and between thelarche and regular periods, was associated with increased dense area, even after adjusting for childhood weight (p trend = 0.013 and 0.028, respectively), and was independent of age at pubertal onset. Conclusions Greater prepubertal weight and earlier pubertal onset are associated with lower adult breast density, but age at pubertal onset does not appear to have an independent effect on adult density after controlling for childhood adiposity. A possible effect of pubertal tempo on density needs further investigation.